Hubungan Dukungan Sosial Dengan Kebermaknaan Hidup Remaja Panti Asuhan Ade Irma Suryani Nasution - Flora Silalahi; Husna, Asmaul (CV. Utility Project Solution, 2023)
This study aims to determine the relationship between social support and the meaning of life in adolescents who live in the Panti Asuhan Ade Irma Suryani Nasution, Medan City. This study uses a quantitative approach. The sample of this study was 35 teenagers at Panti Asuhan Ade Irma Suryani Nasution, Medan City, the sampling technique was purposive sampling. This study uses a Likert scale model. The analysis technique used is Product Moment correlation. The results of this study indicate the rxy correlation coefficient = 0.982 with p = 0,000 (p <0.050), meaning that there is a positive relationship between social support and the meaning of life in adolescents who live. With these results, the study hypothesis in this study is that there is a positive relationship between social support and the meaning of life in adolescents who live. The positive correlation coefficient indicates that the direction of the relationship between the two variables is positive, meaning that the higher the social support, the higher the meaning of life. Social support effectively contributes 96.4% on the meaning of life. The empirical mean of the meaning of life was 84.843 while the empirical mean of social support is 88.88, then for the hypothetical mean variable the meaning of life was 107.5 and the hypothetical mean social support variable was 112.5. Reviewing the results of the study was declared acceptable.